2017
DOI: 10.3389/fmicb.2017.00027
|View full text |Cite
|
Sign up to set email alerts
|

Tight Coupling of Glaciecola spp. and Diatoms during Cold-Water Phytoplankton Spring Blooms

Abstract: Early spring phytoplankton blooms can occur at very low water temperatures but they are often decoupled from bacterial growth, which is assumed to be often temperature controlled. In a previous mesocosm study with Baltic Sea plankton communities, an early diatom bloom was associated with a high relative abundance of Glaciecola sequences (Gammaproteobacteria), at both low (2°C) and elevated (8°C) temperatures, suggesting an important role for this genus in phytoplankton-bacteria coupling. In this study, the tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…Typically, OTUs affiliated with Gammaproteobacteria such as Glaciecola spp. proliferate at higher temperatures (von Scheibner et al, 2017). Gammaproteobacteria also increased in relative abundance in warming experiments of bacterioplankton amended with dissolved organic nitrogen sources and incubated in higher temperatures (Vaquer-Sunyer et al, 2015).…”
Section: Temperature and Phmentioning
confidence: 93%
See 1 more Smart Citation
“…Typically, OTUs affiliated with Gammaproteobacteria such as Glaciecola spp. proliferate at higher temperatures (von Scheibner et al, 2017). Gammaproteobacteria also increased in relative abundance in warming experiments of bacterioplankton amended with dissolved organic nitrogen sources and incubated in higher temperatures (Vaquer-Sunyer et al, 2015).…”
Section: Temperature and Phmentioning
confidence: 93%
“…Glaciecola spp. and also measured metabolic activity of these populations (Brettar et al, 2006;Glaubitz et al, 2014;von Scheibner et al, 2017). Importantly, shifts in abundance of these particular populations were typically coupled to pronounced changes in metabolic activity when exposed to environmental disturbance.…”
Section: Bacterioplankton Community Functioning Is Correlated With Comentioning
confidence: 99%
“…These studies demonstrated selective grazing on large metabolically active bacteria by heterotrophic flagellate grazers. Size-selective predator-prey interactions have also been shown for Glaciecola, that first became abundant upon rapid utilization of phytoplankton derived DOM and subsequently declined in their abundance due to grazing (von Scheibner et al, 2017). It was suggested that once abundant, Glaciecola became a target for size selective predation by protists, including heterotrophic nanoflagellates (HNF) due to their above-average cell size.…”
Section: Tdom Effects On the Coastal Microbial Food Webmentioning
confidence: 99%
“…Several studies have examined the ability of bacteria to degrade the seasonally available phytoplankton derived DOM and found that an increase of such carbon sources influences both the structure and the activity of the bacterial community (Pinhassi et al, 2004;Sapp et al, 2007;Teeling et al, 2012). Especially a versatile group of Gammaproteobacteria, belonging to the order Alteromonadales, responds immediately both in abundance and activity, when phytoplankton derived DOM becomes available (Eilers et al, 2000;McCarren et al, 2010;Pedler et al, 2014;Beier et al, 2015;von Scheibner et al, 2017). Only few studies have investigated the effects of terrestrial derived DOM on marine microbial community structure and activity (Herlemann et al, 2014(Herlemann et al, , 2017Blanchet et al, 2017;Traving et al, 2017), of which even less have been conducted in the coastal Arctic (Sipler et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the genus Glaciecola has been suggested as an early marker (responder) of oil pollution and an oil degrading Glaciecola strain has previously been isolated (Chronopoulou, Sanni et al 2015, Krolicka, Boccadoro et al 2017). On the other hand, this genus has also been suggested to be one of the dominant consumers of phytoplankton-derived organic matter during a cold-water spring bloom (von Scheibner, Sommer et al 2017).…”
Section: Dominant Generalists and Phytoplankton-associated Taxamentioning
confidence: 99%